E-health literacy as a mediator on relationship between predictors and online health information-seeking behaviour among government employees in Putrajaya, Malaysia - Mazlan, Azriey (2020)
It has been widely accepted that the internet has become one of the main sources of health information and provides vast amount of information for the promotion of healthy lifestyles. The level of a person’s eHealth literacy will determine how much they will benefit from the online health information obtained and provide the efforts to improve the efficiency of the healthcare system and health outcomes. This study specifically investigates predictor namely direct experience, salience of unmet health information needs, beliefs internet self-efficacy, information carrier characteristics of trust in internet health information, information carrier utility factor of internet health information seeking and the role of eHealth Literacy as the mediation effect on the relationship between all the predictors and online health information seeking behaviour (OHISB). The Comprehensive information seeking model (CMIS) and eHealth Literacy (eHeals) provided the theoretical foundation for this study. The study was designed as quantitative study. The data was collected from 387 government employees at Putrajaya, Malaysia from 5 ministries and agencies through self-administered questionnaire over a period of 2-month. The multistage sampling technique was employed in gathering the participants. The examination of the research questions and hypotheses, relevant parts of the survey for each questions or hypotheses were done through statistical tests. Descriptive statistics such as frequency, means and standard deviations were used to provide a better understanding of all the variables. The data were analyzed using Structural Equation Model (SEM). To examine the construct validity and reliability of the model, Confirmatory Factor Analysis (CFA) was used. Finding shows that there were significant relationship between internet self-efficacy belief, trust in internet health information (ICC) and internet health information seeking (ICUF) and OHISB. However, direct experience and salience of unmet information needs did not show significant relationship towards OHISB. Finding also shows that eHealth literacy mediated all the predictor on OHISB accept salience of unmet information needs. Thus, it can be concluded that eHealth literacy is important on all forms of online health information seeking.